Positive electrode active material for lithium-ion secondary batteries
The lithium-containing transition metal oxide with specific compositional and structural characteristics effectively addresses the issue of cation mixing in lithium-ion secondary batteries, enhancing their rate characteristics and discharge capacity.
Patent Information
- Application Number
- JP2022125668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2042-08-05
AI Technical Summary
Existing lithium-ion secondary batteries with nickel and manganese as positive electrode active materials suffer from suppressed lithium reinsertion and reduced output characteristics due to cation mixing, especially when Ni cations are mixed into Li cation sites.
A lithium-containing transition metal oxide with the compositional formula Li_a Ni_x Mn_y O_2, where a is 1.10 or more, 0.48≦x≦0.52, and y=1-x, is developed. This oxide has a peak integral intensity ratio of I(003)/I(104) of 1.5 or more and a crystallite diameter of 100 nm or less, which helps suppress cation mixing and enhance rate characteristics.
The proposed positive electrode active material significantly improves the rate characteristics of secondary batteries by reducing cation mixing and maintaining high discharge capacity even at high current values.
Smart Images

Figure 0007666445000001
Abstract
Description
[Technical field]
[0001] The technology disclosed in this specification relates to a positive electrode active material for a lithium ion secondary battery. [Background technology]
[0002] Lithium ion secondary batteries (hereinafter simply referred to as secondary batteries) contain nickel and manganese as the positive electrode active material and have a close-packed structure of oxygen. x Ni 0.5 Mn 0.5 Studies have been conducted on transition metal oxides containing lithium, such as O2 (X≧1) (Patent Document 1).
[0003] The lithium-containing transition metal oxide described in Patent Document 1 has a crystal structure attributed to a hexagonal system, and an X-ray diffraction image of the crystal structure has a peak P003 assigned to the (003) plane and a peak P104 assigned to the (104) plane. As the lithium-containing transition metal oxide absorbs and releases lithium, an integrated intensity ratio I 003 / I 104 However, it has the characteristic that it changes reversibly within the range of 0.7 to 1.5. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2008-258160 A Summary of the Invention [Problem to be solved by the invention]
[0005] In the positive electrode active material of the positive electrode, when Ni cations are mixed into the Li cation sites (so-called cation mixing), the reinsertion of lithium ions into the sites is suppressed, and the output characteristics of the secondary battery are reduced. Patent Document 1 discloses that the lithium-containing transition metal oxide suppresses cation mixing, but sufficient rate characteristics have not yet been obtained.
[0006] The technique disclosed in this specification provides a positive electrode active material that can further improve the rate characteristics of a secondary battery. [Means for solving the problem]
[0007] The present specification discloses a positive electrode active material for a secondary battery. a Ni x Mn y The lithium-containing transition metal oxide is represented by the formula: O2 (a≧1.10, 0.48≦x≦0.52, y=1-x). In an X-ray diffraction image of this lithium-containing transition metal oxide, the peak integrated intensity ratio I(003) / I(104) of the peak assigned to the (003) plane to the peak assigned to the (104) plane in the X-ray diffraction image is 1.5 or more, and the crystallite size based on the peak assigned to the (003) plane is 100 nm or less.
[0008] Since the lithium-containing transition metal oxide has the above characteristics, it is possible to provide a secondary battery that is excellent in rate characteristics, that is, discharge characteristics at a high current value. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The positive electrode active material of the secondary battery disclosed in this specification has the above-mentioned peak integrated intensity ratio: I(003) / I(104) of 1.5 or more, so that it is considered that the incorporation of Ni cations into the Li cation sites is reduced, and the factors that inhibit the conduction by Li cations are reduced. Note that the above description is an inference regarding the action of the positive electrode active material disclosed in this specification, and does not restrict the disclosure of this specification.
[0010] Hereinafter, the lithium-containing transition metal oxide (hereinafter, simply referred to as oxide), which is the positive electrode active material disclosed in this specification, will be described.
[0011] (Lithium-containing transition metal oxides) The oxide disclosed in this specification is represented by the following composition formula (hereinafter also referred to as formula (1)). Li a Ni x Mn y O2(a≧1.10, 0.48≦x≦0.52, y=1-x) (1)
[0012] In formula (1), a is 1.10 or more. The number of elements of Ni and Mn is "x+y", which is 1, so a indicates the number of elements of Li relative to the number of elements of Ni and Mn, which is 1. When a is 1.10 or more, Li cation sites are present more predominantly than Ni and Mn, enabling high-rate discharge and making it easier to obtain high rate characteristics (capacity retention rate due to high-rate discharge).
[0013] a is, for example, 1.10, for example, 1.11, for example, 1.12, for example, 1.13, for example, 1.14, for example, 1.15, for example, 1.16, for example, 1.17, for example, 1.18, for example, 1.19, for example, 1.20, for example, 1.21. The upper limit of a is not particularly limited, but is, for example, 1.20. The range of a can be set by arbitrarily combining the above upper limit value and lower limit value.
[0014] In formula (1), x represents the number of Ni elements, and satisfies x+y (the number of Mn elements)=1. x is 0.480 or more and 0.520 or less. x is, for example, 0.485 or more, for example, 0.490 or more, for example, 0.495 or more, for example, 0.500 or more, for example, 0.505 or more, for example, 0.510. x is, for example, 0.515 or less, for example, 0.510 or less, for example, 0.505 or less, for example, 0.500 or less, for example, 0.495 or less, or for example, 0.490 or less. The range of x can be set by arbitrarily combining the above upper limit value and lower limit value.
[0015] In formula (1), y represents the number of Mn elements, and satisfies x (the number of Ni elements) + Y = 1. For example, y is 0.480 or more and 0.520 or less. For example, y is 0.485 or more, for example, 0.490 or more, for example, 0.495 or more, for example, 0.500 or more, for example, 0.505 or more, for example, 0.510. For example, y is 0.515 or less, for example, 0.510 or less, for example, 0.505 or less, for example, 0.500 or less, for example, 0.495 or less, or for example, 0.490 or less. The range of y can be set by arbitrarily combining the above upper limit value and lower limit value.
[0016] In formula (1), the number of oxygen atoms is two, but this does not necessarily mean that the number of oxygen atoms is two, and represents a value close to two.
[0017] (Characteristics in X-ray diffraction patterns) (integrated intensity ratio) The oxide represented by formula (1) has a peak attributable to the (003) plane and a peak attributable to the (104) plane in its X-ray diffraction pattern. The peak integrated intensity ratio of these peaks: I(003) / I(104) is 1.5 or more.
[0018] In this specification, the X-ray diffraction image can be obtained by powder X-ray measurement using Cu-Kα as a radiation source. For example, in the X-ray diffraction image, the peaks attributable to the (003) plane and the (104) plane of the hexagonal crystal structure belonging to the space group R-3m in Miller indices hkl can be identified by a conventional method. For example, powder X-ray diffraction measurement is performed in the range of diffraction angle 2θ=10 to 90°, and Rietveld analysis is performed to determine the crystal structure and its space group, and the peaks attributable to the (003) plane and the peaks attributable to the (104) plane can be identified.
[0019] Furthermore, the ratio of the integrated intensity I(003) of the peak assigned to the (003) plane to the integrated intensity I(104) of the peak assigned to the (104) plane, i.e., the integrated intensity of the diffraction peak of the (003) plane / the integrated intensity of the diffraction peak of the (104) plane, can be determined by a conventional method.
[0020] This integral intensity ratio is also an index of cation mixing, and when the integral intensity ratio is high, for example, it is said that the layer structure is less disturbed by cation mixing and is well developed. When the integral intensity ratio is 1.5 or more, the movement of Ni cations to the Li cation sites is suppressed, and the rate characteristics can be improved. On the other hand, when the integral intensity ratio exceeds 2.00, the orientation is shown in a specific direction, so that the direction of insertion and removal of Li cations during charging and discharging becomes limited, and the rate characteristics may decrease.
[0021] The integrated intensity ratio is, for example, more than 1.50, for example, 1.51 or more, for example, 1.55 or more, for example, 1.60 or more, for example, 1.65 or more, for example, 1.65 or more, for example, 1.70 or more, for example, 1.75 or more, or for example, 1.80 or more. Considering the anisotropy of the orientation, the integrated intensity ratio is, for example, 2.00 or less, for example, 1.90 or less, for example, 1.85 or less, for example, 1.80 or less, for example, 1.75 or less, or for example, 1.70 or less. The range of the integrated intensity ratio can be set by arbitrarily selecting these lower limit and upper limit values, for example, 1.50 or more and 2.0 or less, for example, more than 1.50 and 1.80 or less, or for example, more than 1.50 and 1.70 or less.
[0022] (Crystallite size) The lithium-containing transition metal oxide has a crystallite size of 100 nm or less based on the peak assigned to the (003) plane in the X-ray diffraction pattern already described. By making the crystallite size 100 nm or less, the diffusion distance of Li cations within the crystal can be shortened while maintaining the crystallinity of the oxide. At the same time, the introduction of Li cations can be prevented from becoming non-uniform during firing of the oxide, and thus the incorporation of Ni cations into the Li cation sites can be prevented.
[0023] The crystallite size can be calculated by determining the half-width of the peak attributable to the (003) plane and then using the Scherrer formula. The calculation of the crystallite size using the Scherrer formula is well known to those skilled in the art.
[0024] The crystallite size is, for example, 95 nm or less, for example, 90 nm or less, for example, 85 nm or less, for example, 80 nm or less. The lower limit of the crystallite size is not particularly limited, but is, for example, 70 nm or more, for example, 75 nm or more, for example, 80 nm or more, for example, 85 nm or more.
[0025] (Method of producing lithium-containing transition metal oxide) The oxides disclosed herein can be synthesized by synthesizing a precursor by a co-precipitation method and then calcining the precursor.
[0026] (Precursor synthesis) <Preparation of raw materials> The precursor is obtained as a precipitate by a coprecipitation method. As the precursor, for example, it may be advantageous to use a hydroxide from which an oxide can finally be obtained in the subsequent calcination. As the hydroxide, a raw material mixture or an aqueous solution thereof is prepared by blending a Ni raw material such as Ni salt and a Mn raw material such as Mn salt in a ratio (molar ratio) such that the metal components of the oxide other than Li, i.e., Ni and Mn, are the desired element ratios of x and y in formula (1). Here, the Ni raw material and the Mn raw material can be sulfates, nitrates, chlorides, etc. In addition, since these raw materials are preferably highly water-soluble, hydrates of these salts can be used as appropriate. Typically, they are nickel sulfate hexahydrate and manganese sulfate pentahydrate.
[0027] The choice of whether to use the raw material mixture or its aqueous solution for preparing the precursor is appropriately determined taking into consideration the generation of by-products, solubility, and the like.
[0028] <Precursor (precipitate) preparation process> Next, a hydroxide precipitate is obtained from this raw material mixture or its aqueous solution by the so-called coprecipitation method as a precursor for firing.
[0029] It may be advantageous to use an alkali metal hydroxide such as sodium hydroxide as it is or in an aqueous solution (for example, an aqueous solution of about 20% by mass to 50% by mass) for these raw material mixtures or their aqueous solutions to generate precipitates with a controlled target pH of 11.20 to 12.00. By setting the target pH in this range, the crystallinity of the oxide obtained can be increased and the increase in crystallite size can be suppressed. If the pH is less than 11.20, the primary particle size of the precursor becomes large, so the crystallite size of the oxide also becomes large, and if the crystallite size is large, the diffusion distance of Li cations becomes long, so the rate characteristics may decrease. If the pH exceeds 12.00, the primary particle size of the precursor becomes too small, so the crystallinity of the oxide decreases, leading to a decrease in discharge capacity. In addition, the primary particles aggregate to increase the secondary particle size, so the rate retention may decrease. Preferably, the target pH is 11.40 to 11.80.
[0030] In addition, it may be advantageous to set the target pH fluctuation range of the precipitation solution for preparing the precursor to less than ±0.20. If the fluctuation range is ±2.0 or more, the size of the primary particles of the precursor becomes non-uniform, and Li is introduced non-uniformly in the subsequent calcination step, which makes it easier for cation mixing to occur. Preferably, the pH fluctuation range relative to the target pH is, for example, ±0.18 or less, for example, ±0.16 or less, for example, ±0.14 or less, or for example, ±0.12 or less.
[0031] In adjusting the pH to a target value and adjusting the pH range, it may be advantageous to use an aqueous solution of an alkali metal or an inorganic acid of the same type as the metal salt used as a raw material.
[0032] In the precipitation liquid, the ammonium ion concentration is also adjusted. The ammonium ion concentration is not particularly limited, but is adjusted to, for example, 3 to 2 g / l. Examples of the aqueous solution that supplies ammonium ions include aqueous solutions of ammonia water, ammonium sulfate, ammonium chloride, ammonium carbonate, and ammonium fluoride.
[0033] The reaction temperature in the coprecipitation method may be, for example, 10°C or higher, preferably 20°C or higher, and 60°C or lower, and other known conditions may be appropriately adopted. The molar concentration of the metal in the precipitation solution in the coprecipitation method is not particularly limited, but may be, for example, 0.1 mol / l to 2.5 mol / l. The coprecipitation method may be either a batch method or a continuous method. The above coprecipitation method may be carried out while introducing an inert gas such as argon gas, carbon dioxide gas, or nitrogen gas into the precipitation solution.
[0034] When a sufficient amount of Ni-Mn hydroxide precipitate is obtained in the precipitate-forming solution, the precipitate is washed with water or the like, dried, and separated as a precursor in a conventional manner.
[0035] <Firing process> Next, the obtained precursor is fired. The firing process can include a primary firing process in which only the precursor is fired, and a secondary firing process in which the precursor is fired together with the Li raw material. Therefore, prior to the secondary firing process, a mixing process of the precursor after the primary firing and the Li raw material is provided.
[0036] <First firing process> In the primary firing step, the precursor can be fired at a heating temperature of, for example, 500° C. to 700° C. for, for example, 5 hours to 15 hours, or for example, 10 hours to 14 hours. By this step, excess moisture contained in the precursor can be removed. In the primary firing step, at least a part of the hydroxide as the precursor may be converted to an oxide. In the primary firing step, a non-reducing gas such as air can be used.
[0037] <Mixing process> The mixing step is a step in which the precursor after the primary firing is mixed with a Li raw material containing lithium, such as a lithium compound, to obtain a lithium mixture. The Li raw material is mixed so as to obtain the desired Li ratio in formula (1). Since Li may volatilize during firing, the Li raw material can be mixed with a Li raw material having a greater amount of Li than the intended a value (Li ratio) in advance, taking into account the volatilization.
[0038] The Li raw material is not particularly limited, but it is preferable to use, for example, lithium hydroxide, lithium nitrate, lithium carbonate, or a mixture thereof. In particular, it is preferable to use lithium hydroxide or lithium carbonate in consideration of ease of handling and stability of quality.
[0039] By thoroughly mixing the precursor and the Li raw material, the Li / Me ratio becomes uniform between the individual particles obtained, and the battery characteristics become stable. A general mixer can be used for mixing. For example, a shaker mixer, a Loedige mixer, a Julia mixer, or a V blender can be used.
[0040] <Secondary firing process> The secondary firing process is a process in which the lithium mixture obtained in the mixing process is fired to obtain an oxide (positive electrode active material). In the secondary firing process, firing is performed by gradually lowering the firing temperature. This allows Li to be introduced into the Li / Mn oxide, and by gradually lowering the firing temperature, Li can be diffused slowly and sufficiently into the Li layer while suppressing oxygen deficiency. In addition, Ni and Mn can be retained in the transition metal layer, which suppresses cation mixing and provides excellent rate characteristics.
[0041] In the secondary firing step, the precursor after the primary firing is oxidized and Li can be introduced into the oxide after the primary firing by heating at a first temperature of, for example, 800°C or more and 1200°C or less, or for example, 900°C or more and 1100°C or less, or for example, 1000°C for, for example, 8 hours or more and 20 hours or less, 10 hours or more and 16 hours or less, or for example, 10 hours or more and 14 hours.
[0042] Furthermore, in the secondary firing step, the mixture is heated at a temperature lower than the first temperature, for example, at a temperature of 750° C. to 950° C., or at a second temperature of 800° C. to 900° C., for example, for 6 hours to 14 hours, or for example, for 8 hours to 12 hours, or for example, for 9 hours to 11 hours, and further heated for 8 hours to 20 hours, 10 hours to 16 hours, or for example, for 10 hours to 14 hours.Further, the mixture is heated at a temperature lower than the second temperature, for example, at a third temperature of 600° C. to 800° C., or at a temperature of 650° C. to 750° C., for example, for 6 hours to 14 hours, or for example, for 8 hours to 12 hours, or for example, for 9 hours to 11 hours. Furthermore, the mixture is heated at a fourth temperature which is lower than the third temperature, for example, 100°C or more and 300°C or less, for example, 120°C or more and 180°C or less, or for example, 140°C or more and 160°C or less, for example, for 10 hours or more and 30 hours or less, for example, 15 hours or more and 25 hours or less, or for example, 18 hours or more and 22 hours or less.
[0043] In this way, by performing baking at the first temperature, the second temperature, the third temperature, and the fourth temperature, it is possible to obtain a positive electrode active material that reliably suppresses cation mixing and exhibits excellent rate characteristics. Note that, although the first to fourth temperatures are adopted, the present invention is not limited thereto, and a secondary baking step may be performed in which the baking temperature is gradually lowered by adopting the first, second, and fourth temperatures, or the first, third, and fourth temperatures.
[0044] The temperature increase and decrease rates in the secondary firing step are not particularly limited, but are preferably, for example, 2° C. / min to 10° C. / min, and more preferably 5° C. / min to 10° C. / min. The firing atmosphere is preferably an oxidizing atmosphere such as air.
[0045] The above-mentioned firing process can produce an oxide. The resulting oxide powder can be crushed as necessary. EXAMPLES
[0046] Hereinafter, specific examples embodying the disclosure of this specification will be described, but the disclosure of this specification is not limited to the following specific examples. EXAMPLES
[0047] In this example, for the oxide represented by formula (1), a precursor was obtained by coprecipitation under the conditions shown in Table 1, and then heated at 600°C for 12 hours (first firing step in this specification), and then fired at the temperature and for the time shown in the firing pattern in Table 1 (second firing step in this specification). Details of the operations for each production example (hereinafter simply referred to as the examples) and comparative examples are shown below.
[0048] [Example 1] Nickel (II) sulfate hexahydrate and manganese (II) sulfate pentahydrate were dissolved in pure water to a ratio of 1.8 mol / L, Ni:Mn=0.50:0.50 (mol). 1 L of 10 g / L ammonia solution was prepared in a reaction vessel, and a precipitate was generated using a sodium hydroxide solution so that the pH was within 11.20±0.14, and a precursor was obtained by coprecipitation. The precursor was calcined in air at 600°C for 12 hours. Next, the precursor and Li2CO3 were mixed so that the ratio of Li to Ni+Mn was 1.25, and then calcined in air at 1000°C for 12 hours. Thereafter, the temperature was gradually lowered while maintaining the temperature at 850°C for 10 hours, 700°C for 10 hours, and 150°C for 20 hours, to obtain an oxide (positive electrode active material).
[0049] [Example 2] A positive electrode active material was obtained in the same manner as in Example 1, except that the pH setting value during coprecipitation was 11.60 and the pH fluctuation range was ±0.12.
[0050] [Example 3] A positive electrode active material was obtained in the same manner as in Example 1, except that the pH setting value during coprecipitation was 12.00 and the pH fluctuation range was ±0.12.
[0051] [Example 4] A positive electrode active material was obtained in the same manner as in Example 2, except that the precursor that had been subjected to the first firing step and Li2CO3 were mixed so that the ratio of Li to Ni+Mn was 1.30 and the pH fluctuation range was ±0.13.
[0052] [Example 5] A positive electrode active material was obtained in the same manner as in Example 2, except that nickel (II) sulfate hexahydrate and manganese (II) sulfate pentahydrate at the time of coprecipitation were dissolved in pure water so that Ni:Mn was 0.48:0.52 (mol) and the pH fluctuation range was ±0.14.
[0053] [Example 6] A positive electrode active material was obtained in the same manner as in Example 2, except that nickel (II) sulfate hexahydrate and manganese (II) sulfate pentahydrate at the time of coprecipitation were dissolved in pure water so that Ni:Mn was 0.52:0.48 (mol) and the pH fluctuation range was ±0.14.
[0054] [Comparative Example 1] A positive electrode active material was obtained in the same manner as in Example 2, except that the pH fluctuation range during coprecipitation was set to within ±0.22.
[0055] [Comparative Example 2] A positive electrode active material was obtained in the same manner as in Example 1, except that the pH setting value during coprecipitation was 12.20.
[0056] [Comparative Example 3] A positive electrode active material was obtained in the same manner as in Example 1, except that the pH setting value during coprecipitation was 11.00 and the pH fluctuation range was ±0.10.
[0057] [Comparative Example 4] A positive electrode active material was obtained in the same manner as in Example 2, except that the pH fluctuation range was set to ±0.13, and in the secondary baking step, the material was baked in air at 1000° C. for 12 hours and then held at 150° C. for 20 hours.
[0058] [Comparative Example 5] The pH fluctuation range was set to ±0.15, and in the second firing step, a positive electrode active material was obtained in the same manner as in Example 2, except that firing was carried out at 1000 °C for 24 hours in the atmosphere.
[0059]
Table 1
Examples
[0060] For the oxide (positive electrode active material) prepared in Example 1, evaluations were made on the following items. The results are also shown in Table 1.
[0061] <Li / (Ni + Mn) ratio, Ni (mol%), Mn (mol%)> For the oxides obtained in Examples 1 to 6 and Comparative Examples 1 to 4, composition analysis was performed using a multi-type ICP emission spectrometer (ICPE-9000 manufactured by Shimadzu Corporation) to obtain quantitative values of Li, Ni, and Mn.
[0062] <Crystallite size and integrated intensity ratio> Powder X-ray diffraction measurements were performed on the oxides obtained in Examples 1 to 6 and Comparative Examples 1 to 4. The measurement conditions were as follows: using Cu-Kα rays, scanning was performed at 2θ = 10 to 120° at a scan rate of 5° / min. The crystallite size was calculated using Scherrer's equation from the half-width of the peak attributed to the (003) plane of the space group R-3m obtained near 2θ = 18.6°. Also, the integrated intensity I(003) of the peak attributed to the (003) plane and the integrated intensity I(104) of the peak attributed to the (104) plane were determined, and the integrated intensity ratio: I(003) / I(104) was calculated.
[0063] <Discharge capacity and rate retention rate> A secondary battery for evaluation was produced to measure the discharge capacity and rate retention rate by a charge-discharge test. The oxides obtained in Examples 1 to 6 and Comparative Examples 1 to 4 were used as the positive electrode active material, and the conductive assistant (acetylene black) and binder (PVDF) were weighed out so that the mass ratio of active material:conductive assistant:binder was 85:10:5. NMP was added so that the solid content rate was 38 mass%, and mixed in a mortar. Then, the mixture was kneaded at 2000 rpm and 20 min using a foam remover mixer (ARE-310 manufactured by Thinky) to produce an electrode slurry. The obtained electrode slurry was applied with a blade having a gap of 150 μm, dried at 100° C. for 30 minutes, and then the positive electrode layer was punched out with a hand punch having a diameter of 16 mm. The electrode density was 2.5 g / cm 3 . 3 The positive electrode layer was obtained by pressing the positive electrode layer so that it was pressed into a positive electrode layer. In a glove box with an Ar atmosphere, the positive electrode layer, the separator (polyethylene porous film, thickness 15 μm), and the metallic Li foil (diameter 19 mm, thickness 1 mm) prepared in the 2032 coin battery were laminated, and the electrolyte (1.1 M LiPF6 / ethylene carbonate:dimethyl carbonate = 30:70 / 0.1 M LiDFOB) was introduced, and the battery was sealed with a crimping machine.
[0064] A charge and discharge test was carried out using the secondary battery for evaluation obtained as described above. After constant current-constant voltage charging and discharging at a set voltage of 4.5V or 3.0V and a rate of 0.1C for 2 cycles, the battery was charged at a constant current-constant voltage of 4.5V and a rate of 0.1C, and then discharged at a constant current of 3.0V and a rate of 5C to obtain the 0.1C discharge capacity, the 5C discharge capacity, and the ratio of the 5C discharge capacity to the 0.1C discharge capacity (referred to as the rate retention rate).
[0065] As shown in Table 1, when the pH fluctuation is 0.20 or more, the size of the primary particles of the precursor becomes non-uniform, so that Li is introduced non-uniformly in the second firing step, and it was found that cation mixing is likely to occur (Comparative Example 1).
[0066] In addition, the pH during synthesis by the coprecipitation method determines the balance between nucleation and growth of the precursor, and the higher the pH, the more dominant the nucleation becomes, and the smaller the primary particles of the precursor become. The size of the primary particles of the precursor is one of the factors that determine the crystallite size of the active material. It was found that when the pH is higher than 12.0, the primary particles of the precursor become excessively small, and the crystallinity of the active material decreases, resulting in a decrease in discharge capacity. It was also found that the particles are aggregated together, and the secondary particle diameter of the precursor and active material increases, resulting in a decrease in rate characteristics (rate retention rate). (Example 3, Comparative Example 2) On the other hand, when the pH is lower than 11.2, the primary particles of the precursor become large, and the crystallite size of the active material also becomes large. It was found that when the crystallite size is large, the diffusion distance of Li increases, resulting in a decrease in output characteristics. (Example 1, Comparative Example 3)
[0067] It was found that cation mixing could be suppressed by gradually lowering the temperature after firing at 1000°C in the secondary firing process (Examples 1 to 6, Comparative Example 4). This was thought to be because such a firing pattern suppressed oxygen deficiency and also suppressed Ni from being mixed into the Li site by sufficiently diffusing Li into the Li layer.
[0068] In addition, in the secondary firing process, firing at 1000°C for 24 hours was performed to promote crystal growth and suppress cation mixing. As a result, it was found that if the crystallite size becomes large, the diffusion distance of Li ions becomes longer, resulting in a decrease in rate characteristics (Comparative Example 5).
[0069] From the above, it was found that by using an oxide as a positive electrode active material having a Li / Ni+Mn of 1.10 or more, an I(003) / I(104) integrated intensity ratio of 1.50 or more, and a crystallite size based on the peak assigned to the (003) plane of 100 nm or less, a good 5C capacity can be ensured, an excellent rate retention rate can be obtained, and a secondary battery with excellent rate characteristics can be obtained.
[0070] It was also found that by setting the target pH to 11.20 or higher and 12.00 or lower, with the pH fluctuation range being within ±0.20, when preparing the precursor by the co-precipitation method, and by gradually lowering the temperature during the secondary firing process, it is possible to obtain an oxide with a predetermined integrated intensity ratio and crystallite size, thereby suppressing cation mixing and maintaining the crystallite size within a preferred range, thereby suppressing the decrease in discharge capacity and improving the rate characteristics (rate retention rate).
Claims
[Claim 1] Li a Ni x Mn y O 2 (1.10≦a≦1.20, 0.48≦x≦0.52, y=1−x), A positive electrode active material having a peak integrated intensity ratio, I(003) / I(104), of a peak assigned to a (003) plane and a peak assigned to a (104) plane obtained from an X-ray diffraction image of 1.50 to 1.70, and a crystallite size based on the peak assigned to the (003) plane of 85 nm to 100 nm.
Citation Information
Patent Citations
Cobalt-free positive electrode material and application thereof
CN113839030A
Lithium nickel manganese oxide, its manufacturing method and lithium-ion secondary cell using the same
JP2004002141A
Active material for nonaqueous electrolyte secondary battery, and its manufacturing method
JP2008258160A
Active material for nonaqueous electrolyte secondary battery, electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2013069583A
Positive electrode active material for lithium secondary battery, electrode for lithium secondary battery, lithium secondary battery
JP2014049239A